Using 2-(N-Methyl-N-Phenylamino) acetonaphthone as photoinitiator for the polymerization of methyl methacrylate - Keskin, Sevnur; Arsu, Nergis (SPRINGER, 2006)
2-(N-Methyl-N-phenylamino) acetonaphthone (MPA) was synthesized as a cleavable photoinitiator and the structure of the photoinitiator was confirmed by spectral and elemental analysis. MPA shows a much higher molar absorptivity than the commercially used acetophenone derivative. The photoinitiation capability of MPA was demonstrated by using methyl methacrylate and a formulation containing multifunctional monomers. Incorporation of the naphthoyl moiety into the polymer was demonstrated by spectroscopic methods.
Keywords: SPECTROSCOPY; Polymer Science